Respuesta :

Method 1: Algebraically find f(g(x)) first and then plug in x = 5
f(x) = 6x+3
f(g(x)) = 6*[ g(x) ] + 3
f(g(x)) = 6*(x-4) + 3
f(g(x)) = 6x-24+3
f(g(x)) = 6x-21
f(g(5)) = 6*5-21
f(g(5)) = 9

OR

Method 2: Find g(5) first and plug that into x of f(x)
g(x) = x-4
g(5) = 5-4
g(5) = 1
So f(g(5)) is equivalent to f(1)
f(x) = 6x+3
f(1) = 6*1+3
f(1) = 9

We get the same answer following either method.

------------------------------------------------------------------------

Final Answer: 9

ACCESS MORE